Peran Literasi Digital dalam Meningkatan Hasil Belajar Sejarah Kebudayaan Islam Siswa MA Al Mufid Teluk Pandan Tahun Pelajaran 2023/2024 - Jufri, Abdurrahman (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
The digital era has demanded rapid adaptation in the education sector, where information is accessible in real-time, anytime, and anywhere. The advancement in science and technology requires educators to grasp the digital world to create an effective learning environment that enhances students' abilities and creativity. Digital literacy has become a fundamental skill essential for teaching and learning activities, including sourcing, identifying, accessing, evaluating, and integrating information. This study aims to (1) explore how digital literacy can improve the learning outcomes of Islamic History and Culture for students at MA Al Mufid Teluk Pandan for the 2023/2024 academic year, and (2) identify the supporting and inhibiting factors affecting the role of digital literacy in enhancing learning outcomes. A qualitative descriptive approach was employed to describe strategies for improving digital literacy competencies in Islamic History and Culture education. Data was collected through observations, interviews, and documentation, with data validity ensured by data reduction, presentation, and conclusion drawing. The study found that (1) digital literacy implementation involved using available digital media such as social media, the internet, e-books, and smartphones, as well as digital applications like WhatsApp, Google Classroom, and YouTube in the learning process. (2) Supporting factors included training workshops, IT facilities like computers, LCDs, Wi-Fi, and data package subsidies, while inhibiting factors comprised unstable internet connections and geographical distances. (3) The evaluation of digital literacy implementation in Islamic History and Culture learning involved several stages: planning with lesson plans aligned with learning objectives, execution using necessary technology to maximize learning, and evaluation through assigning tasks to students.